The Influence of Public Relations on Consumer Purchasing Decisions: Study on CV. Ranjang 69 Garut - Mulia, Hari (International Journal for Educational and Vocational Studies, 2019)
This research is motivated by consumer purchasing decisions on CV. Ranjang 69 Garut which has decreased in the past few years based on sales data from the marketing department and found several problems that occur in the field. This can be caused by several things, namely the desire of different consumers in choosing the ramen noodle shop, consumer tastes that are constantly changing along with the increasing number of similar products, unpleasant experiences of consumers who have consumed them, store locations that are less visible to consumers, consumers are less sure to buy the product, the influence of information from consumers who have bought is negative, consumers feel less satisfied with the product so they do not make repeat purchases. Based on the analysis, the results obtained that the research instrument used in this study was declared valid because it has a value of> 0.30 and is reliable because the research instruments from public relations have a value of > 0.553 and the research instruments from consumer purchasing decisions have a value > 0.444. From the results of the correlation coefficient test obtained information that public relations has a moderate influence on consumer purchasing decisions with a correlation value of 0.542 and the magnitude of the test coefficient of determination to determine the contribution of public relations to consumer purchasing decisions by 26.5% and the remaining 73.5%.Respondents about public relations on CV. Beds 69 Garut is included in the agreed category, as well as the responses of respondents about consumer purchasing decisions on CV. Ranjang 69 Garut is included in the agreed category as well.